Nursing Performance In-Home Visits - Frutalegio da Costa Freitas, Aureo; Faria, Ana; Manuela Ferreira Pereira da Silva Martins, Maria; João R. Oliveira, Maria (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The nurse's action, in home visits to patients, is essential to ensure quality care and greater proximity to patients who receive care at home. Health is understood as a state of complete physical, mental, and social well-being, and not just the absence of disease or other pathologies. This means that health must be seen more broadly, considering not only the physical state of the individual, but also their emotional and social well-being. Objectives: to know the activities of Nursing in the community and the indicators associated with it; to know the activities with the highest incidence reported by the nurses who work there. Method: a scoping review was carried out, a systematic review of the literature and published manuscripts, where they were identified regarding the location of the studies, defined in the MEDLINE database (Medical Literature Analysis and Retrieval System Online – US National Library of Medicine's), the articles included were published between August 1, 2018 and January 1, 2023. Result and Discussion: In addition, it is important that nurses, who work in the home area, receive training in patient safety and risk management that may arise. They need to be aware of these safety risks in home settings and be able to identify and mitigate them to ensure patient safety. Conclusion: Nursing care, which emphasizes health promotion and disease prevention, is essential to improve patients' quality of life and prevent other health complications. It is important that nurses continue to focus on these aspects of nursing care and educate patients about the importance of taking care of their health. That is why pedagogical methodologies and knowledge of nursing activities in the community, and their associated indicators, are important factors to train new nurses to be well trained and prepared to act effectively in the community where they are called to exercise their duties, their knowledge in the field of health